The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1002/advs.202308797
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of N‐ to M‐Polar Switching in Ferroelectric Al1−xScxN Capacitors

Roberto Guido,
Haidong Lu,
Patrick D. Lomenzo
et al.

Abstract: Ferroelectric wurtzite‐type aluminum scandium nitride (Al1−xScxN) presents unique properties that can enhance the performance of non‐volatile memory technologies. The realization of the full potential of Al1−xScxN requires a comprehensive understanding of the mechanism of polarization reversal and domain structure dynamics involved in the ferroelectric switching process. In this work, transient current integration measurements performed by a pulse switching method are combined with domain imaging by piezorespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
(125 reference statements)
0
0
0
Order By: Relevance
“…The complex extrinsic nature of the ferroelectric switching process involving domain nucleation and domain wall motion is widely accepted. , The switching kinetics in ferroelectrics are determined by the relative contributions of domain nucleation and domain wall motion. When unrestricted sideways expansion of ferroelectric domains can be achieved after nucleation, the time-dependent normalized switched polarization follows the Kolmogorov–Avrami–Ishibashi (KAI) model Δ P norm = Δ P false( t false) 2 P s = 1 e true( t / t 0 true) n where P s is the spontaneous polarization, t 0 is the characteristic switching time, and n is the Avrami exponent, which is related to the effective dimension of domain growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex extrinsic nature of the ferroelectric switching process involving domain nucleation and domain wall motion is widely accepted. , The switching kinetics in ferroelectrics are determined by the relative contributions of domain nucleation and domain wall motion. When unrestricted sideways expansion of ferroelectric domains can be achieved after nucleation, the time-dependent normalized switched polarization follows the Kolmogorov–Avrami–Ishibashi (KAI) model Δ P norm = Δ P false( t false) 2 P s = 1 e true( t / t 0 true) n where P s is the spontaneous polarization, t 0 is the characteristic switching time, and n is the Avrami exponent, which is related to the effective dimension of domain growth.…”
Section: Resultsmentioning
confidence: 99%
“…We note that even if not discussed explicitly in the present analysis, grain boundaries represent another possible source of domain wall pinning and, hence, domain wall creep motion. PFM studies showed that ferroelectric domains in fluorite- and wurtzite-structured thin films encounter several grain boundaries during their sideways expansion and that larger lateral domain wall velocities can be achieved by increasing the grain size in fluorite-structured ferroelectrics. The character of the grain boundary, and hence the crystalline regularity between neighboring grains, affects the way in which domain walls move . In contrast to Al 0.85 Sc 0.15 N in which the grains have a similar crystallite orientation along the direction of the applied field, the different crystallite orientations between neighboring Hf 0.5 Zr 0.5 O 2 grains may significantly slow down or even impede the domain wall motion for subcoercive applied electric field magnitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation